Possible Barriers Affecting Implementation of ISO28000 for the Supply Chain - Chong, Yee Chin; Sorooshian, Shahryar (ExcelingTech Pub, UK, 2019)
This paper is objective to examine the barrier of ISO28000 implementation. As more and more supply chain process faced disruption and delay due to accident, importance of supply chain security management attract the concern from top management of organization. ISO 28000 is a standard that released in 2007 which specify requirement for security management system for the supply chain. However, there are still many organization didn’t apply for this standard. Also, very few, if any, studies have worked on the barriers of this standard. Therefore, past research results about barrier for related ISO standards are reviewed to assist determine the barrier of ISO 28000 implementation. After evaluate the possible barrier, 16 barriers for ISO28000 implementation is identified and explained.